Promoting trans patient autonomy in surgical preparation for phalloplasty and metoidioplasty: results from a community-based cross-sectional survey and implications for preoperative assessments - Leo L. Rutherford; Elijah R. Castle; Noah Adams; Logan Berrian; Linden Jennings; Ayden Scheim; Aaron Devor; Nathan J. Lachowsky (BMC Medical Ethics)
Abstract Background Some transgender and nonbinary people undergo phalloplasty and/or metoidioplasty as part of their medical transition process. Across surgical disciplines, a variety of resources are used to assist patients who are preparing for surgeries, including educational materials, workshops, peer support, and lifestyle changes. For gender-affirming surgeries, patients undergoing assessments to discern whether they are ready to undergo the surgery, and to assist them in achieving preparedness when needed. Little research investigates what resources are useful in helping patients to feel prepared to undergo phalloplasty or metoidioplasty, and how assessments and resources can promote patient autonomy in the process. Respect for patient autonomy is one of the central tenets of ethical healthcare, yet historically, scholarship related to pre-surgical assessments for gender-affirming surgery has focused determining the ideal surgical candidate rather than respecting patient autonomy and ascertaining individual patient needs. Methods This study sought to fill this gap by utilizing data from PROGRESS (Patient-Reported Outcomes of Genital Reconstruction and Experiences of Surgical Satisfaction), a cross-sectional, community-based survey of trans and nonbinary adults from the United States of America and Canada who had undergone one or more of these surgeries. Results Results revealed most participants (86%, n = 186) felt prepared to undergo surgery, though the majority of our sample (53%, n = 105) did not find referral letter assessments to be helpful. Peer support such as online resources/blogs were rated as highly useful, along with surgical consults. In a multivariable logistic regression, higher perceived preparedness was associated with identifying as queer (inclusive of gay, bi and pansexual compared to being straight), and feeling that one’s assessment process was useful (as opposed to not useful). Type of assessment was not significantly associated with preparedness; therefore, what is most useful when preparing for surgery may vary across individuals. Conclusion Healthcare professionals who interact with preparing patients should develop new or utilize existing resources to assist patients in identifying their preparation needs and achieving preparedness. Our data supports assessments that center surgical care planning rather than assessing level of gender dysphoria. Future longitudinal research could further refine which assessment processes are most effective in helping patients who are preparing for these surgeries. Assessments should ensure that patients are appropriately prepared to undergo and recover from surgery through a robust process of informed consent.